Pengembangan Instrumen Tes Literasi Numerasi Berbasis Etnomatematika untuk Siswa SMP Negeri 2 Jambi - Dewi, Sri; Defitriani, Eni (Universitas Batanghari Jambi, 2024)
Numeracy literacy skills are the most important part of the abilities that every student must have. The limited number of numeracy literacy instruments at SMP Negeri 2 Jambi is one of the factors causing less than optimal mathematics learning. Students are still lacking in understanding questions, formulating, identifying and interpreting mathematical problems properly and correctly. To train these abilities, an ethnomathematics-based numeracy literacy test instrument is needed. This research aims to describe the process of developing an ethnomathematics-based numeracy literacy test instrument and determine the validity index of the ethnomathematics-based numeracy literacy test instrument. This research is development research that adapts the Plomp model which consists of initial assessment stage, design stage, realization/construction stage, and test, evaluation and revision stage. Data collection techniques in this research are field note techniques, questionnaire techniques, validation techniques and test techniques with research instruments in the form of field note sheets, questionnaire sheets, validation sheets and test questions. Data analysis uses Aiken's formula and empirical validity uses product moment correlation. The results of this research show that at the design stage, there was a difference of opinion between the two validators regarding the grid, there was one indicator question that was not in accordance with basic competencies. These differences are then analyzed and revised according to input and suggestions from the validator. The researcher improved the question grid as well as the test questions, resulting in good question items, and the results of content validation by 4 expert validators calculated using the Aiken's formula obtained a validity value of 0.785. These results indicate that the ethnomathematics-based numeracy literacy test instrument is declared valid from three aspects, namely; materials, constructs and language.